nargiza COGNITIVE APPROACH IN TEACHING A FOREIGN LANGUAGE AS A MOTIVATIONAL TOOL: COGNITIVE APPROACH IN TEACHING A FOREIGN LANGUAGE AS A MOTIVATIONAL TOOL - Bo’riyeva, Nargiza (Журнал иностранных языков и лингвистики, 2022)
The purpose of this article is to analyze the cognitive approach in teaching a foreign language to students as a means of increasing their motivation. The set goal determines the solution of the following tasks: defining this approach in teaching, identifying the features of use, as well as the role of foreign, scientists in the development of its principles. The hypothesis of the study is that the cognitive approach used in the classroom provokes a change in the dynamics of the educational process and serves as a motivational tool for students. Awareness of this makes you be prepared for the fact that at the next stage of the lesson you will have to change tactics. However, the teacher’s knowledge of the laws of the cognitive process gives a sense of self-confidence, allows you to model the educational process adequately to the tasks set.